EFEKTIVITAS EDUKASI PEMBUKUAN DASAR DAN PENINGKATAN LITERASI KEUANGAN SISWA SMK IPTEK - Sri Putri Winingrun; Muliyani; Intan Rahma Sari (Publika Citra Media, 2026)
Financial literacy among Indonesian youth remains low; for example, a 2024 survey reports a national financial literacy index of only around 65.4%. Vocational high school (SMK) students, as future workforce and entrepreneurs, require basic bookkeeping skills for personal financial management. This community service program provided education in basic bookkeeping as a foundation of personal financial management. Activities included financial literacy education, training in recording simple transactions, guided bookkeeping practice, and evaluation of learning outcomes. Post-program evaluation showed significant improvements in participants’ financial knowledge and bookkeeping abilities. Students gained a better understanding of debit-credit concepts, ledgers, and trial balances, and became proficient in using technology tools (e.g. spreadsheets or basic accounting software) for financial record-keeping. These results are consistent with similar service programs reporting enhanced student competence in using digital accounting applications after training. The program underscores the importance of financial literacy education and practical bookkeeping as foundational competencies for youth financial management.